Tice: A real‐time language compilable using C++ compilers. (5th October 2020) - Prastowo, Tadeus; Palopoli, Luigi; Abeni, Luca
Summary: Model‐based development (MBD) holds the promise to capture potential timing problems in embedded software during the early phases of the development, securing the production of bug‐free embedded software. For most MBD approaches, the source code is just an intermediate artifact that can be generated automatically from the models. This assumption clashes with an undeniable fact: a large share of the commercial embedded software exploits existing libraries or is developed using C/C++ natively. A way to reconcile the ambitions of MBD with the use of a programming language is by offering new language constructs and an innovative compilation tool‐chain that prevents model error and timing problems "by construction." However, the persistent popularity of C/C++ among embedded programmers and the limited availability of tools have severely limited the uptake of alternative programming languages for embedded software. Therefore, we propose an original route. Our language proposal, named Tice, has been shaped as a C++ active library. Tice retains full compatibility with existing C++ code, which can be integrated easily into new Tice‐based projects. The enforcement of Tice syntax and semantics can be made by a standard C++ compiler, forgoing the need for new tools. In this article, we describe Tice's syntax, semantics, and model of computation and communication. We demonstrate Tice's practical applicability on an industrial scale use‐case and give ample evidence for Tice's efficient compilation using off‐the‐shelf C++ compilers. Finally, we show Tice's code generation process.